Unity 3D Augmented Reality Learning Media for Vehicle Component Recognition to Improve Students’ Learning Enthusiasm with Intellectual Disabilities - Zinnurain; Ani Endriani; Haromain (Jurnal Ilmiah Sekolah Dasar, 2026)
Students with intellectual disabilities often experience difficulties in understanding concepts comprehensively, especially those that are abstract. This is caused by the limited use of innovative and interactive learning media. This study aims to develop and examine the effectiveness of Unity 3D based augmented reality learning media in increasing the learning enthusiasm of students with intellectual disabilities. This study employs a Research and Development (R&D) method using the ADDIE model, which is limited to the implementation stage. The research subjects consisted of 31 students and 2 teachers. Data collection techniques included needs analysis, expert validation, and teacher and student response questionnaires using validation sheets and Likert-scale-based instruments. Data were analyzed using descriptive quantitative methods. The results indicate that the developed media falls into the “very feasible” category based on media expert validation (92%) and material expert validation (90%), and received very positive responses from students (86%) and teachers (91%). The conclusion of this study confirms that the Unity 3D based augmented reality learning media is feasible and effective in enhancing students’ learning enthusiasm and engagement. The implication of this study suggests that augmented reality can serve as a strategic alternative in inclusive learning to provide more concrete, interactive, and meaningful learning experiences.